Environment-friendly aluminum dust suppressant and preparation method thereof
By using dust inhibitors composed of L-malic acid, sodium polyacrylate, chitosan, rhamnola, glycerol and ethylene glycol, the problem of hydrogen reaction between aluminum dust and water is solved, and the effect of efficient dust suppression and hydrogen suppression is achieved, while also having environmental protection and recycling-friendly characteristics.
Patent Information
- Application Number
- CN202510034302.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
When existing dust inhibitors inhibit aluminum dust, they can easily cause aluminum dust to react with water to produce hydrogen, which poses a risk of explosion, and has secondary pollution problems, which is not conducive to the recycling and utilization of aluminum dust.
An environmentally friendly aluminum dust suppressor composed of L-malic acid, sodium polyacrylate, chitosan, rhamnolipid, glycerol and ethylene glycol is used to form a chemical adsorption film and physical agglomeration structure through the synergistic effect of these components, blocking the direct contact between aluminum dust and water and inhibiting the production of hydrogen.
It effectively inhibits the flying of aluminum dust and the production of hydrogen, improves the safety of industrial production, and does not affect the recycling of aluminum dust, and has good environmental friendliness.
Smart Images

Figure CN119823721A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dust prevention and control, and specifically relates to an environmentally friendly aluminum dust suppressant and a preparation method thereof. Background Art
[0002] In industrial production, aluminum is widely used, but the aluminum dust produced during its processing is not only prone to cause pneumoconiosis and respiratory diseases, but also prone to explosion due to its high activity, posing a serious threat to personnel and production safety. Existing dust suppression technologies have insufficient research on the suppression of aluminum dust. Although the surfactants in most dust suppressants help suppress dust, they easily cause aluminum dust to react with water to produce hydrogen, which poses an explosion risk and secondary pollution problems, which is not conducive to the recycling of aluminum dust. Therefore, it is urgent to develop dust suppressants that are efficient, environmentally friendly, and can suppress both dust and hydrogen. Summary of the invention
[0003] The purpose of the present invention is to provide an environmentally friendly aluminum dust suppressant and a preparation method thereof. The preparation method is simple, and the prepared dust suppressant can effectively suppress the flying of aluminum dust, reduce its harm to the environment and human body, and at the same time inhibit its reaction with water to produce hydrogen, thereby improving the safety of industrial production.
[0004] To achieve the above-mentioned purpose, the present invention provides an environmentally friendly aluminum dust suppressant, which is composed of the following raw materials in percentage by mass: 0.1%-0.3% L-malic acid, 0.4%-0.6% sodium polyacrylate, 0.7%-0.9% chitosan, 1%-3% rhamnolipid, 0.5%-0.7% glycerol, 0.4%-0.6% ethylene glycol, and the remaining component is deionized water.
[0005] Preferably, the dust suppressant is composed of the following raw materials in percentage by mass: 0.15% L-malic acid, 0.5% sodium polyacrylate, 0.8% chitosan, 2% rhamnolipid, 0.63% glycerol, 0.56% ethylene glycol, and the remaining component is deionized water.
[0006] To achieve the above object, the present invention also provides a method for preparing the above environmentally friendly aluminum dust suppressant, comprising the following steps:
[0007] S1. Weigh each component by mass percentage; put deionized water into a heating device, control the temperature at 30-40°C, then add L-malic acid to the preheated deionized water, and stir evenly until it is completely dissolved to obtain an L-malic acid aqueous solution;
[0008] S2, adding sodium polyacrylate to the solution obtained in step S1, stirring evenly until completely dissolved, to obtain an aqueous solution containing L-malic acid and sodium polyacrylate;
[0009] S3, adding chitosan to the solution obtained in step S2, stirring until the chitosan is fully dissolved, to obtain an aqueous solution containing L-malic acid, sodium polyacrylate and chitosan;
[0010] S4, adding rhamnolipid to the solution obtained in step S3, stirring until the rhamnolipid is completely dissolved, to obtain an aqueous solution in which L-malic acid, sodium polyacrylate, chitosan and rhamnolipid are dissolved;
[0011] S5, adding glycerol to the solution obtained in step S4, stirring until the glycerol is completely dissolved, to obtain an aqueous solution in which L-malic acid, sodium polyacrylate, chitosan, rhamnolipid and glycerol are dissolved;
[0012] S6. Add ethylene glycol to the solution obtained in step S5, and stir until the ethylene glycol is completely dissolved to obtain an environmentally friendly aluminum dust suppressant.
[0013] Preferably, in step S1, the stirring speed is 1200 rpm, the stirring time is 10 min; the temperature is controlled at 35°C; L-malic acid is added to deionized water in batches to better observe the contact process and dissolution of L-malic acid and water, and the L-malic acid solution is added first to make the overall solution acidic, which is convenient for the dissolution of insoluble substances such as chitosan.
[0014] Preferably, in step S2, the stirring speed is 1200 rpm, the stirring time is 15 min, and the dripping speed of sodium polyacrylate is 0.1-0.2 ml / min. Sodium polyacrylate, as a high molecular weight sodium salt, plays an important role in improving the viscosity and stability of the product; and sodium polyacrylate should still be added slowly to observe the degree of solubility of sodium polyacrylate and L-malic acid.
[0015] Preferably, in step S3, the stirring speed is 1200 rpm and the stirring time is 20 min; chitosan is added to the solution obtained in step S2 in batches; this addition method helps to control the dispersion process of chitosan and avoid particle agglomeration caused by rapid addition.
[0016] Preferably, in step S4, the stirring speed is 1200 rpm, and the stirring time is 30 min; the dropping speed of rhamnolipid is 0.2-0.3 g / min; this addition method helps to better disperse the rhamnolipid and accelerate its dissolution process.
[0017] Preferably, in step S5, the stirring speed is 1200 rpm, and the stirring time is 10 min; the dripping speed of glycerol is 0.3-0.5 mL / min; this addition method helps to better disperse the glycerol and accelerate its dissolution process.
[0018] Preferably, in step S6, the stirring speed is 1200 rpm, the stirring time is 10 min, and the dropping speed of ethylene glycol is 0.3-0.5 mL / min. This addition method helps to better disperse the ethylene glycol and accelerate its dissolution process.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] (1) The present invention utilizes the carboxyl functional group (-COOH) of L-malic acid to complex with aluminum atoms on the surface of aluminum powder particles, thereby causing L-malic acid molecules to form a thicker chemical adsorption film on the surface of aluminum particles. This film isolates aluminum from direct contact with water and blocks the path for aluminum and water to react to generate hydrogen. At the same time, L-malic acid can provide an acidic environment to make polysaccharides (chitosan) more easily dissolve.
[0021] (2) The sodium polyacrylate used in the present invention not only has the characteristics of stabilizing the solution but also has good water absorption and adhesion, and can also enhance surface wettability and dust adhesion.
[0022] (3) The present invention utilizes the active groups on the chitosan molecular chain to promote the dust to form large aggregates through physical or chemical adsorption, increase the weight of the particles, and reduce their ability to suspend in the air. At the same time, after the solution captures the dust, the evaporation of water will form a film with both flexibility and strength on the surface of the dust, effectively covering the dust source and suppressing the flying of dust.
[0023] (4) The present invention utilizes the properties of rhamnolipid as a biosurfactant to reduce the surface tension of water, thereby promoting wetting and agglomeration of hydrophobic dust.
[0024] (5) The present invention uses propylene glycol as a humectant to increase the wettability of the captured dust, while ethylene glycol is used as an antifreeze agent to maintain the fluidity of the solution at low temperatures.
[0025] In summary, the present invention achieves significant dust suppression and hydrogen suppression effects through the synergistic effect between the raw materials. At the same time, the hydroxyl, carboxyl and other groups of each component in the dust suppressant enhance the attraction between particles through hydrogen bonds, covalent bonds and the like, and the long-chain molecular structure plays a bridging role, so that the dust forms a more stable agglomeration structure, further improving the dust suppression efficiency. Experiments have verified that the dust suppressant prepared by the present invention has good environmental friendliness, providing an efficient, stable and environmentally friendly solution for aluminum dust suppression. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a comparison chart of hydrogen production between the dust suppressant prepared in Example 1 and water;
[0027] Figure 2 This is a graph of hydrogen suppression efficiency of the dust suppressant prepared in Example 1;
[0028] Figure 3 This is a comparison chart of the dust suppressant prepared in Example 1 and the aluminum powder after spraying with water;
[0029] Figure 4 This is a dust suppression efficiency diagram of the dust suppressant prepared in Example 1;
[0030] Figure 5 This is a curve chart showing the effects of the dust suppressant prepared in Example 1, tap water and Hoagland's nutrient solution on wheat seed growth. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0032] Example 1
[0033] An environmentally friendly aluminum dust suppressant is composed of the following raw materials in percentage by mass: 0.15% L-malic acid, 0.5% sodium polyacrylate, 0.8% chitosan, 2% rhamnolipid, 0.63% glycerol, 0.56% ethylene glycol, and the remaining component is deionized water.
[0034] The preparation method of the environmentally friendly aluminum dust suppressant of this embodiment comprises the following steps:
[0035] S1. Add 96.35 mL of deionized water to a dry, clean container, and place the container on a magnetic stirrer. The magnetic stirrer can provide a uniform stirring effect. Set the stirrer speed to 1200 rpm and the solution temperature to 35 °C. Then add 0.15 g of L-malic acid to the solution in batches, and continue to stir the solution with a magnetic stirrer for 10 minutes. L-malic acid will gradually dissolve under stirring and appropriate temperature conditions, and eventually form a uniform L-malic acid aqueous solution. At this time, the solution is in acidic conditions, which is more suitable for the dissolution of chitosan.
[0036] S2, adding 0.5 g of sodium polyacrylate to the solution obtained in step S1 at a dropping speed of 0.1-0.2 ml / min, and slowly adding the sodium polyacrylate to help the sodium polyacrylate gradually mix with the L-malic acid aqueous solution, and then continue to stir on a magnetic stirrer for 15 minutes to obtain an aqueous solution in which L-malic acid and sodium polyacrylate are dissolved;
[0037] S3, adding 0.8 g of chitosan to the solution obtained in step S2 in batches, and then continuously stirring on a magnetic stirrer for 20 min until the chitosan is fully dissolved, ensuring that the chitosan can be fully dissolved in the solution to form an aqueous solution uniformly dissolved with L-malic acid, sodium polyacrylate and chitosan;
[0038] S4, adding 2 g of rhamnolipid to the solution obtained in step S3 at a dropping speed of 0.2-0.3 g / min, and continuing to stir with a magnetic stirrer for 30 min until the rhamnolipid is completely dissolved, to obtain an aqueous solution containing L-malic acid, sodium polyacrylate, chitosan and rhamnolipid;
[0039] S5, adding 0.5 mL of glycerol to the solution obtained in step S4 at a dropping speed of 0.3-0.5 ml / min, and then continuing to stir on a magnetic stirrer for 10 min until the glycerol is completely dissolved. By this continuous stirring method, it can be ensured that the glycerol is completely dissolved in the aqueous solution, and then the glycerol is evenly distributed in the solution to obtain an aqueous solution in which L-malic acid, sodium polyacrylate, chitosan, rhamnolipid and glycerol are dissolved;
[0040] S6. Add 0.5 mL of ethylene glycol to the solution obtained in step S5 at a dropping speed of 0.3-0.5 ml / min, and then continue stirring on a magnetic stirrer for 10 min until the ethylene glycol is completely dissolved to obtain an environmentally friendly aluminum dust suppressant.
[0041] The dust suppressant prepared in this example was tested for hydrogen suppression effect, and the test process and results are as follows:
[0042] 1) Use a high-precision electronic balance (accuracy up to 0.001g) to accurately weigh two aluminum powder samples, each weighing 1.500g.
[0043] 2) Place a weighed aluminum powder sample in a clean and pre-treated (high-temperature drying) 250mL reaction container, and seal the container; add 200mL of deionized water to the reaction container as a control group to test the reaction behavior of aluminum powder in a pure water environment. Place another weighed aluminum powder sample in another clean and pre-treated (high-temperature drying) 250mL reaction container, and seal the container. Add 200mL of the dust suppressant prepared in Example 1 to the reaction container as an experimental group. The experiment was carried out at normal atmospheric pressure (101.325kPa) and 45 degrees Celsius (318.15K).
[0044] 3) After adding the respective reaction media, the hydrogen measuring device was immediately started to monitor the change in the concentration of hydrogen generated by the aluminum powder reaction within 2 hours in real time, and the change in the hydrogen concentration in reaction vessel 1 (control group) and reaction vessel 2 (experimental group) was recorded respectively, and the hydrogen concentration C (ppm) was calculated based on these data.
[0045] In order to ensure the reliability and repeatability of the experimental results, the above process was conducted three independent experiments, each time using a new aluminum powder sample and reaction medium to avoid the influence of residual substances, and the data of each experiment were recorded, including the changes in hydrogen concentration in the control group and the experimental group.
[0046] Calculate the volume fraction f (unit: %) according to the hydrogen concentration C (ppm):
[0047] f=C×10 -6
[0048] Calculate the number of moles of hydrogen n (unit: mol) by volume fraction f:
[0049] n=f·P·V / R·T
[0050] Where P is the pressure (101.325 kPa); R is the ideal gas constant (0.0821 L·atm / (K·mol)).
[0051] The experimental results are shown in Table 1 and Figure 1 and Figure 2 As shown:
[0052] Table 1 Comparison of average molar number results between the control group and the experimental group
[0053]
[0054] From Table 1 and Figure 1-2 It can be seen that the average molar number of hydrogen in the experimental group (using dust suppressant) is significantly lower than that in the control group (using pure water). In three independent experiments, the average molar number of hydrogen in the control group was between 6.707-6.713 mol, while the experimental group was stable in the range of 1.483-1.493 mol. The experimental group has a high hydrogen suppression efficiency, indicating that the dust suppressant of the present invention can effectively block the path of aluminum powder and water to generate hydrogen, greatly reducing the risk of aluminum dust explosion caused by hydrogen generation in a humid environment, and significantly improving the safety of industrial production. This is due to the complexation of L-malic acid with the surface of aluminum powder particles, which successfully isolates aluminum from direct contact with water and effectively suppresses the generation of hydrogen.
[0055] The dust suppression effect of the dust suppressant prepared in this example was tested, and the test process and results are as follows:
[0056] 1) Use a dust environment simulation test platform, which mainly includes a fan, a transverse airflow duct, an experimental generator and a spraying device. Turn on the fan, start the dust generator, and adjust the aluminum powder emission concentration of the dust generator to 10.23 mg / m 3 and set the wind speed to 10m / s.
[0057] 2) After the dust generator is started, the spraying device is started to spray pure water evenly in the aluminum dust generating device (control group), and the dispersed aluminum dust concentration Cn after spraying pure water is measured using a dust concentration tester.
[0058] 3) Start the dust generator again, start the spraying device, and evenly spray the dust suppressant prepared in Example 1 into the aluminum dust generating device (experimental group). Use a dust concentration tester to measure the dispersed aluminum dust concentration Cs after spraying the dust suppressant prepared in Example 1.
[0059] 4) Calculate the dust suppression rate η dust suppression by the formula: η dust suppression = (Cn-Cs) / Cn×100%.
[0060] In order to ensure the reliability and repeatability of the experimental results, the above process was carried out three independent experiments, each time using new aluminum powder samples and dust suppressants to avoid the influence of residual substances. The data of each experiment was recorded, including the aluminum dust concentration Cn when spraying pure water and the aluminum dust concentration Cs after spraying the dust suppressant, as well as the corresponding dust suppression rate.
[0061] After 3 independent experiments, the dust suppression efficiency data obtained by taking the average value are shown in Table 2 and Figure 3 and Figure 4 As shown:
[0062] Table 2 Comparison of dust suppression effects between the control group and the experimental group
[0063]
[0064]
[0065] From Table 2 and Figure 3-4 It can be seen that in three independent experiments, the aluminum dust concentration Cn after spraying pure water was between 8.95-9.10 mg / m 3 The aluminum dust concentration Cs after spraying dust suppressant is only 0.52-0.58 mg / m 3 The average dust suppression efficiency reached 93.98%. This fully demonstrates that the dust suppressant has a strong ability to suppress the flying of aluminum dust. Through the synergistic effect of multiple components such as chitosan to promote dust agglomeration, sodium polyacrylate to enhance adhesion, and rhamnolipid to promote wetting and agglomeration, it effectively reduces the amount of aluminum dust suspended in the air, reduces the harm to the environment and human body, and provides an efficient solution for aluminum dust pollution control.
[0066] The dust suppressant prepared in this example was tested for its environmental friendliness, and the test process and results are as follows:
[0067] 1) 25 intact wheat seeds without insect holes or shriveled seeds were selected; the seeds were placed in 3 different culture dishes with corresponding labels, each of which had a paper towel; the dust suppressant prepared in Example 1 (experimental group), tap water (control group 1) and Hoagland's nutrient solution (control group 2) were added to the three culture dishes respectively, ensuring that the paper towels were completely wet.
[0068] 2) Once the wheat seeds have successfully germinated and taken root, transfer them to a specially made wheat growing container and use a wet towel to keep the bottom of the container moist to ensure that the wheat always stays hydrated during its growth.
[0069] 3) During the entire observation period, the growth of the wheat plants was monitored and recorded.
[0070] The observation and record results are shown in Table 3 and Figure 5 .
[0071] Table 3 Comparison of the cumulative weight of wheat plants between the two control groups and the experimental group
[0072]
[0073]
[0074] From Table 3 and Figure 5 It can be found that in the wheat seed growth experiment, the experimental group using dust suppressants has a cumulative gram weight growth trend of wheat plants compared with the tap water control group and the Hoagland nutrient solution control group, and is significantly better than the tap water control group. This shows that the dust suppressant of the present invention has good environmental friendliness. While suppressing aluminum dust, its ingredients will not have a significant negative impact on plant growth. In actual application scenarios, even if the dust suppressant remains or spreads to the surrounding environment, it will not cause harm to plants in the ecological environment. It has good environmental friendliness, which further proves its feasibility and advantages as an environmentally friendly dust suppressant.
[0075] Example 2
[0076] An environmentally friendly aluminum dust suppressant is composed of the following raw materials in percentage by mass: 0.1% L-malic acid, 0.4% sodium polyacrylate, 0.7% chitosan, 1% rhamnolipid, 0.5% glycerol, 0.4% ethylene glycol, and the remaining component is deionized water.
[0077] The preparation method of the environmentally friendly aluminum dust suppressant in this embodiment remains consistent with that in Example 1.
[0078] The dust suppressant prepared in this example was tested for hydrogen suppression effect, dust suppression effect and environmental friendliness effect, respectively. The test process was consistent with that in the example, and the test results were similar to those in Example 1.
[0079] Example 3
[0080] An environmentally friendly aluminum dust suppressant is composed of the following raw materials in percentage by mass: 0.3% L-malic acid, 0.6% sodium polyacrylate, 0.9% chitosan, 3% rhamnolipid, 0.7% glycerol, 0.6% ethylene glycol, and the remaining component is deionized water.
[0081] The preparation method of the environmentally friendly aluminum dust suppressant in this embodiment remains consistent with that in Example 1.
[0082] The dust suppressant prepared in this example was tested for hydrogen suppression effect, dust suppression effect and environmental friendliness effect, respectively. The test process was consistent with that in the example, and the test results were similar to those in Example 1.
Claims
1. An environmentally friendly aluminum dust suppressant, characterized in that: The dust suppressant is composed of the following raw materials in percentage by mass: 0.1%-0.3% L-malic acid, 0.4%-0.6% sodium polyacrylate, 0.7%-0.9% chitosan, 1%-3% rhamnolipid, 0.5%-0.7% glycerol, 0.4%-0.6% ethylene glycol, and the remaining component is deionized water.
2. The environmentally friendly aluminum dust suppressant according to claim 1, characterized in that: The dust suppressant is composed of the following raw materials in percentage by mass: 0.15% of L-malic acid, 0.5% of sodium polyacrylate, 0.8% of chitosan, 2% of rhamnolipid, 0.63% of glycerol, 0.56% of ethylene glycol, and the remaining component is deionized water.
3. A method for preparing an environmentally friendly aluminum dust suppressant as described in any one of claims 1-2, characterized in that: The following steps are involved: S1. Weigh each component by mass percentage; put deionized water into a heating device, control the temperature at 30-40°C, then add L-malic acid to the preheated deionized water, and stir evenly until it is completely dissolved to obtain an L-malic acid aqueous solution; S2, adding sodium polyacrylate to the solution obtained in step S1, stirring evenly until completely dissolved, to obtain an aqueous solution containing L-malic acid and sodium polyacrylate; S3, adding chitosan to the solution obtained in step S2, stirring until the chitosan is fully dissolved, to obtain an aqueous solution containing L-malic acid, sodium polyacrylate and chitosan; S4, adding rhamnolipid to the solution obtained in step S3, stirring until the rhamnolipid is completely dissolved, to obtain an aqueous solution in which L-malic acid, sodium polyacrylate, chitosan and rhamnolipid are dissolved; S5, adding glycerol to the solution obtained in step S4, stirring until the glycerol is completely dissolved, to obtain an aqueous solution in which L-malic acid, sodium polyacrylate, chitosan, rhamnolipid and glycerol are dissolved; S6. Add ethylene glycol to the solution obtained in step S5, and stir until the ethylene glycol is completely dissolved to obtain an environmentally friendly aluminum dust suppressant.
4. The method for preparing an environmentally friendly aluminum dust suppressant according to claim 3, characterized in that: In step S1, the stirring speed is 1200 rpm, the stirring time is 10 min, the temperature is controlled at 35° C., and L-malic acid is added to deionized water in batches.
5. The method for preparing an environmentally friendly aluminum dust suppressant according to claim 3, characterized in that: In step S2, the stirring speed is 1200 rpm, the stirring time is 15 min, and the dropping speed of sodium polyacrylate is 0.1-0.2 ml / min.
6. The method for preparing an environmentally friendly aluminum dust suppressant according to claim 3, characterized in that: In step S3, the stirring speed is 1200 rpm and the stirring time is 20 min; chitosan is added to the solution obtained in step S2 in batches.
7. The method for preparing an environmentally friendly aluminum dust suppressant according to claim 3, characterized in that: In step S4, the stirring speed is 1200 rpm, the stirring time is 30 min, and the dropping speed of rhamnolipid is 0.2-0.3 g / min.
8. The method for preparing an environmentally friendly aluminum dust suppressant according to claim 3, characterized in that: In step S5, the stirring speed is 1200 rpm, the stirring time is 10 min, and the dripping speed of glycerol is 0.3-0.5 mL / min.
9. The method for preparing an environmentally friendly aluminum dust suppressant according to claim 3, characterized in that: In step S6, the stirring speed is 1200 rpm, the stirring time is 10 min, and the dropping speed of ethylene glycol is 0.3-0.5 mL / min.
Citation Information
Cited By
Dust suppressant as well as preparation method and application thereof
CN121203619A